2020
DOI: 10.3390/s20195566
|View full text |Cite
|
Sign up to set email alerts
|

An Architecture for the Performance Management of Smart Healthcare Applications

Abstract: The sixth-generation (6G) network intends to revolutionize the healthcare sector. It will offer smart healthcare (s-health) treatments and allow efficient patient remote monitoring, exposing the high potential of 6G communication technology in telesurgery, epidemic, and pandemic. Healthcare relies on 6G communication technology, diminishing barriers as time and space. S-health applications require strict network requirements, for instance, 99.999% of service reliability and 1 ms of end-to-end latency. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…The combination of communication, computation and sensing enhances services and business cases. Rather than relying on patched assistance, service providers now expect more efficient and effective security support [54][55][56][57]. Network Latency Issues: It is desired to have a minimal computational delay for dealing with devices and sensors used in the healthcare domain.…”
Section: G and Healthcare Domain: Potential Challenges Addressedmentioning
confidence: 99%
“…The combination of communication, computation and sensing enhances services and business cases. Rather than relying on patched assistance, service providers now expect more efficient and effective security support [54][55][56][57]. Network Latency Issues: It is desired to have a minimal computational delay for dealing with devices and sensors used in the healthcare domain.…”
Section: G and Healthcare Domain: Potential Challenges Addressedmentioning
confidence: 99%
“…5G-VINNI [20], directly addresses satellite integration in 5G networks from the point of view of highly dynamic and flexible network architectures, service deployment and testing, to create new technical and commercial service deployment models, enabling virtualized functions from the network and service layer. Other research works have shown the applicability of these SDN/NFV concepts in mobile networks in a practical way, through developments of testbeds or PoCs [21]- [25], however, none of them was designed to address high dynamic networks.…”
Section: Related Workmentioning
confidence: 99%
“…Além disso, torna-se indispensável a detecção e o diagnóstico precoce da doença, uma vez que, retardar efetivamente seu progresso reduz significativamente o custo dos sistemas de saúde (Levin e Stevens, 2011;Fouad, 2014). Assim, o acompanhamento das informações fisiológicas das pessoas por aplicações de tempo real auxilia os profissionais da saúde na tomada rápida de decisão (Vergütz et al, 2020).…”
Section: Motivaçãounclassified